Study of hot electrons in AlGaN/GaN HEMTs under RF Class B and Class J operation using electroluminescence. Issue 12 (December 2015) - Brazzini, Tommaso; Casbon, Michael A.; Sun, Huarui; Uren, Michael J.; Lees, Jonathan; Tasker, Paul J.; Jung, Helmut; Blanck, Hervé; Kuball, Martin
Abstract: Electroluminescence microscopy and spectroscopy have been used to investigate hot electron concentration and electron temperature during RF operation. Two modes of operation were chosen, Class B and Class J, and compared with DC conditions. Hot electron concentration and temperature were on average lower for both RF modes than under comparative DC conditions. While these average values suggest that degradation due exclusively to hot electrons may be lower for RF than for DC conditions, the peak values in EL intensity and electric field along dynamic load lines have also to be taken into account and these are higher under Class J than Class B. Highlights: Electroluminescence is a good indicator for average hot electron contributions during operation Under RF (Class B and Class J), on average hot electrons have a lower impact compared to DC Peak values might be important in the degradation mechanism Field-driven degradation could be important but not detectable with Electroluminescence, possibly higher under Class J